The economic crisis and its impact on the equity market (Kuala Lumpur Stock Exchange) composite index / Otteran Gira - Gira, Otteran (2001)
Market sentiment weakened severely. The onset of the crisis since July 1997 worsened sentiment in the stock market, which had commenced on its downtrend since April 1997. With the speculative attack on the ringgit and the de facto devaluation of the Thai baht, the depreciation of the ringgit reinforced the downward spiral of the KLSE C1. From the high of 1,271.57 points on 25 February 1997, the KLSE C1 closed at its lowest in 11 years at 263.70 points on 1 September 1998.